Mini-invasive aortic surgery: a 2 years experience - Salcuni, P.; Azzarone, M.; Biasi, et al., L. (Acta Biomedica Atenei Parmensis, 2005)
The aim of this study was to evaluate a less invasive technique for the exposure of the infrarenal aorta and its impact on the treatment of patients with abdominal aortic aneurysms (AAA). Fortyfour patients with AAA were prospectively selected for minilaparotomy aortic exposure and repair using a small periumbilical midline incision, intra-abdominal nondisplaced retraction of the small bowel and conventional hand-sewn vascular anastomosis. Perioperative comparisons with a contemporary group of AAA patients treated with long, open midline incision and extracavitary small bowel retraction were made. There were no significant differences between the minilaparotomy and open surgical control group concerning operating room time, intraoperative and perioperative morbidity or mortality. Significant differences were shown between the two groups regarding intensive care unit stay; the return to a general diet and the length of hospitalization. Minilaparotomy exposure is safe and effective for the treatment of infrarenal AAA. This technique maintains quality outcome while reducing postoperative ileus, hospital stay and resource utilization.